COMPARISON OF THE EFFECTIVENESS OF KEGEL EXERCISE AND MECHANICAL VAGINAL TRAINER IN THE CONSERVATIVE TREATMENT OF PELVIC PROLAPSE IN WOMEN - Татьяна Анатольевна Обоскалова; Марина Игоревна Ярмолинская; Марина Анатольевна Ющенко (The Publishing House Medicine and Enlightenment, 2022)
In 41 patients of the early transition period with POP-Q grade 1 pelvic prolapse, the effectiveness of a mechanical vaginal simulator (group A, n = 21) was studied in comparison with the Kegel exercise (group B, n = 20). The mechanical vaginal trainer compared with the Kegel exercise leads to a lower intensity of clinical symptoms of pelvic prolapse according to the NRS scale (2 (1,5; 2) points in group A and 4 (2; 5) points in group B, U[21;20] = 1021, p = 0,001) and is accompanied by the best compliance according to the modified Morisca-Green test (1 (0; 2) and 1 (0; 2) points, respectively, U[21;20] = 431, p = 0,24).